Akurasi Penggunaan Translation Machine pada Penulisan Sekripsi Mahasiswa - Maslihah, Rizka Eliyana (IAIN Ponorogo, 2018)
Students have thought that with the development of technology world, translation was not longer needed by opening a dictionary to find the meaning of a vocabulary. Simply by entering the source language text into the translation machine, the translator can knew the results of the translation immediately. This was can be applied by everyone. So, it did not require translators to master various translation knowledge. Coupled with the presence of âGoogle Translateâ as a application of translation service, see also students found a solution to solve the translation tasks. But unfortunately, students did not realize that âGoogle Translateâ was only a translation machine that needed to be studied more about the accuracy of the translation results. This research was intended to find out the accuracy of âgoogle translateâ in translating Arabic text into Indonesian, especially in translating educational verses, as well as the impact. And the results of this study stated that all translations using the google translate application had a level of deviation accuracy. So that through this research, it was expected that students realized the weaknesses of âGoogle translateâ, and realized the greve impact after using it for their final task writing.Ø±Ø£Ù Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø¹ÙØ¯ÙØ§ Ø§ÙØØ§Ø¶Ø± Ø£Ù ØªÙØ¯Ù Ø§ÙØªÙÙÙÙÙØ¬ÙØ§ ÙØ¤Ø¯Ù Ø¥ÙÙ Ø¹Ø¯Ù ÙØªØ Ø§ÙÙ Ø¹Ø¬Ù ÙØ¨ØØ« Ù Ø¹Ø§ÙÙ Ø§ÙÙÙÙ Ø§Øª. ÙÙÙÙ Ø¨Ø§ÙØ·ÙØ§Ø¨ ÙØ¹ÙØ§ Ø£Ù ÙØ¯Ø®Ù Ø§ÙÙÙÙ Ø§Øª Ù Ù Ø§ÙÙØºØ© Ø§ÙÙ ØªØ±Ø¬Ù Ø¹ÙÙ Ø¥ÙÙ Ø¢ÙØ© Ø§ÙØªØ±Ø¬Ù Ø©Ø Ø¥Ø° Ø³ÙØ¹Ø±Ù Ø§ÙÙ ØªØ±Ø¬Ù Ø§ÙØªØ±Ø¬Ù Ø© ÙÙØ±Ø§. ÙÙÙ ÙÙ ÙÙØ§Ù ÙÙÙ ÙØ§ØØ¯ Ø¨ÙÙØ°Ø§ Ø§ÙÙØ¹Ù ÙØ³ÙÙÙØ© Ø§Ø³ØªØ®Ø¯Ø§Ù ÙØ°Ù Ø§ÙØ¢ÙØ©. Ø¨Ø§ÙØ¥Ø¶Ø§ÙØ© Ø¥ÙÙ Ø°ÙÙØ ÙØ§ ÙØ´ØªØ±Ø· Ø§ÙÙ ØªØ±Ø¬Ù Ø¨Ø¥ÙÙ Ø§Ù Ø¹ÙÙÙ Ø§ÙØªØ±Ø¬Ù Ø©. ÙØ«Ù Ø© ØØ¶ÙØ± Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø© ÙØ¢ÙØ© Ø§ÙØªØ±Ø¬Ù Ø© ØÙÙÙØ§ ÙØ§Ø³ØªÙÙ Ù ÙØ§Ø¬Ø¨ Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙØªØ±Ø¬Ù Ø©. ÙÙÙÙ Ù Ù Ø§ÙØ£Ø³Ù Ø§ÙØ´Ø¯ÙØ¯Ø ÙØ§ ÙØ¯Ø±Ù Ø§ÙØ·ÙØ§Ø¨ Ø£Ù Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø© ÙÙ ÙÙØ¹ Ù Ù Ø§ÙØ¢ÙØ© ÙØØ³Ø¨Ø ÙØªØØªØ§Ø¬ ÙØ°Ù Ø§ÙØ¢ÙØ© Ø¥ÙÙ Ø§ÙÙØØµ Ø§ÙØ¯ÙÙÙ Ø¹Ù Ø¯ÙØ© Ø¥ÙØªØ§Ø¬ ØªØ±Ø¬Ù ØªÙØ§. ÙÙÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙÙØ´Ù Ø¹Ù Ø§ÙØªØ§Ø¬ Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø© ÙÙ ØªØ±Ø¬Ù Ø© ÙØµÙØµ Ø§ÙØ¬Ù Ù Ù Ù Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© (Ø§ÙØ¢ÙØ© Ø§ÙÙØ±Ø¢ÙÙØ©) Ø¥ÙÙ Ø§ÙÙØºØ© Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ§Ø Ø®Ø§ØµØ© ÙÙ ØªØ±Ø¬Ø© Ø§ÙØ¢ÙØ§Øª Ø§ÙÙ ØªØ¹ÙÙØ© Ø¨Ø¢ÙØ§Øª Ø§ÙØªØ±Ø¨ÙØ©.Â ÙØ£Ù Ø§ Ø§ÙÙØªØ§Ø¦Ø¬ Ù Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø£Ù Ø¥ÙØªØ§Ø¬ Ø§ÙØªØ±Ø¬Ù Ø© Ù Ù Ø®ÙØ§Ù Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø© Ù ÙØØ±ÙØ©. Ø¨Ø§ÙØ¥Ø¶Ø§ÙØ© Ø¥ÙÙ Ø§ÙÙØªØ§Ø¦Ø¬Ø ÙØ±Ø¬Ù Ø¹ÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØ¹Ù Ù Ù Ø¶Ø¹Ù Ø§ÙØªØ±Ø¬Ù Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø©. ÙØ«Ù Ø© Ø§ÙÙØ¹Ù Ù Ù Ø§ÙØ£Ø«Ø± Ø§ÙÙØªÙØ§Ù ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø¬ÙØ¬ÙÙ ÙÙØªØ±Ø¬Ù Ø© Ø®ÙØ§Ù ÙØªØ§Ø¨Ø© Ø§ÙØ¨ØØ« Ø§ÙØ¹ÙÙ Ù.